Patients Have a 15% Redislocation Rate After Arthroscopic Bankart Repair With a Knotless Technique - Emma Abrahams Nattfogel, B.Sc., M.B.B.S; Mats C. Ranebo, M.D., Ph.D (Elsevier, 2024)
Purpose: To evaluate the redislocation rate after arthroscopic Bankart repair (ABR) with a standardized knotless anchor technique in a consecutive series of patients with anterior glenohumeral instability. Methods: Inclusion criteria were patients who underwent ABR by a single surgeon between January 2008 and December 2018 with a minimum follow up of 2 years. We collected data through phone interviews, Western Ontario Shoulder Instability Index, and review of patient records. The primary outcome was redislocation and secondary outcomes were recurrent subluxations, reoperation, postoperative complications, patient satisfaction, and functional outcomes. We also performed survival analysis and risk factor analysis. Results: Of 88 patients (91 shoulders) who underwent ABR during the inclusion period, 70 patients (73 shoulders) were included (follow-up rate 80%). The mean follow-up was 7.5 years (range 2-12 years). Redislocation occurred in 15% (95% confidence interval [CI] 7.8%-25.4%) of patients at a mean of 41 months after surgery (range 6-115 months). The reoperation rate for recurrent redislocation was 4.1%. Overall, 90.4% reported being currently satisfied with their shoulder and the mean Western Ontario Shoulder Instability Index score at follow-up was 73.8% (range 8.3%-99.9%). Patients with redislocation were younger at primary operation than patients with no redislocation (mean 21 years vs 28 years; P = .023) and adjusted hazard ratio for age was 0.86 (95% CI 0.74-0.99; P = .033). It was more common to have less than 3 anchors in patients with redislocation (P = .024), but adjusted hazard ratio was 4.42 (95% CI 0.93-21.02; P = .061). Conclusions: The redislocation rate after ABR with a standardized knotless anchor technique in a consecutive series of patients with anterior glenohumeral instability was found to be 15% after a minimum 2-year follow-up (mean 7.5). Level of Evidence: Level IV, therapeutic case-series.